Five-week sensory motor training program improves functional performance and postural control in young male soccer players - A blind randomized clinical trial - Heleno, L. R.; da Silva, R. A.; Shigaki, L.; Alves Araújo, S. G.; Coelho Candido, C. R.; Alves Okazaki, V. H.; Frisseli, A.; de S. Guerino Macedo, C. (Physical Therapy in Sport, 2016)
Sensory motor training programs are used in the rehabilitation and prevention of injuries among soccer players. Inconsistencies are found in the literature regarding the duration of the protocols and the exercises and equipment used. Objective: To evaluate the benefits of a five-week sensory motor training program on the functional performance and postural control of young soccer players. Methods: The study sample comprised 22 young male soccer players who were evaluated using: the Figure-of-Eight Test (F8), Side Hop Test (SHT), Star Excursion Balance Test (SEBT), and a force platform. The players were randomly divided into a control group (N = 10), who continued their soccer practice sessions and an intervention group (N = 12), who continued their soccer practice sessions and were also enrolled in a supervised five-week sensory motor training program. Results: After the five-week training program, the intervention group obtained significant results in the F8, SHT and SEBT, as well as in the following parameters: area of pressure of sway center (COP), mean velocity and mean frequency of COP. Conclusion: The five-week sensory motor training program, carried out with easily available and low cost equipment, was effective at improving functional performance and postural control in young soccer players.